Risk analysis of poor prognosis and follow-up observation of children with Mycoplasma pneumoniae pneumonia complicated by plastic bronchitis - Zheng, Chunlin; Zheng, Zhidong; Hu, Xiangrong; Huang, Yizhu; Han, Yimin (Frontiers in Pediatrics, 2025)
BackgroundStudies on the risk factors for poor prognosis in pediatric plastic bronchitis (PB) and medium- to long-term follow-up are relatively limited. The aim of this study was to investigate the risk factors for poor prognosis of Mycoplasma pneumoniae pneumonia (MPP) complicated by PB prognosis in children and conduct a detailed follow-up study.MethodsThis was a retrospective study of children diagnosed with MPP complicated by PB at the First Hospital of Putian City from January 2022 to June 2024. Clinical data during hospitalization and after discharge were collected. Patients were assigned to the good prognosis group if both pulmonary imaging and pulmonary function tests one month after discharge were normal or the poor prognosis group if one or both tests were abnormal. Clinical manifestations and laboratory findings were compared between the two groups.ResultsThis study included 62 pediatric patients, with a median age of 8.1 years, of which 35 were male. The poor prognosis group comprised 40 patients (64.5%), and male children accounted for 57.5% (23/40) of this group. Logistic regression analysis indicated that longer fever duration (OR = 2.871) and higher D-dimer level (OR = 1.770) were independent risk factors for poor prognosis in children with PB. ROC curve analysis further revealed that a fever duration of 10.55 days (AUC = 0.852) and a D–dimer level of 5.61 µg/ml (AUC = 0.806) provided optimal prediction of poor prognosis.All patients presented with abnormal pulmonary imaging findings at admission, and 43 (69.4%) had abnormal pulmonary function on the day of discharge; follow-up revealed that 33 patients (53.2%) had abnormal pulmonary imaging findings, and 28 patients (45.2%) had abnormal pulmonary function one month after discharge. Six months after discharge, 13 patients (21.0%) continued to exhibit either pulmonary lesions or impaired pulmonary function.ConclusionA fever duration longer than 10.55 days and a D-dimer level higher than 5.61 µg/ml were independent risk factors for poor prognosis in children with MPP complicated by PB. Children with PB caused by Mycoplasma pneumoniae may experience long-term sequelae, necessitating close follow-up and personalized rehabilitation treatment.